2018
DOI: 10.3390/ma12010089
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Characteristics—Constitutive Equation and Processing Maps—of 21-4N Heat-Resistant Steel

Abstract: The hot deformation behavior of 21-4N heat-resistant steel was studied by hot compression test in a deformation temperature range of 1000–1180 °C, a strain rate range of 0.01–10 s−1 and a deformation degree of 60%, and the stress-strain curves were obtained. The functional relationship between flow stress and process parameters (deformation degree, deformation temperature, strain rate, etc.) of 21-4N heat-resistant steel during hot deformation was explored, the constitutive equation of peak stress was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Huang et al, reported a maximum hot compressive stress value of 350 MPa with material developed through cast product [38]. Similar results of 350 MPa were reported by Li et al, and Ji et al, for 21-4N material developed through the cast process [19,20]. This can be attributed to the fact that inhomogeneous distribution of grain growth from the surface to inner layers occurred during uneven solidification rate.…”
Section: Hot Compression Measurementssupporting
confidence: 58%
See 1 more Smart Citation
“…Huang et al, reported a maximum hot compressive stress value of 350 MPa with material developed through cast product [38]. Similar results of 350 MPa were reported by Li et al, and Ji et al, for 21-4N material developed through the cast process [19,20]. This can be attributed to the fact that inhomogeneous distribution of grain growth from the surface to inner layers occurred during uneven solidification rate.…”
Section: Hot Compression Measurementssupporting
confidence: 58%
“…This non-equilibrium process works based on energizing and quenching, whereby the alloyed materials are brought into the metastable state with the application of pressure and temperature. Moreover, studies related to hot compression for 21-4N were carried out previously using the casting route [18][19][20], whereas hot compression studies of 21-4N steel developed using the powder metallurgy route have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the sample was compressed at high temperature with different  and  . After test, water quenching immediately [35][36] .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the sample was compressed at high temperature with different ε and ε˙. After test, water quenching immediately [44,45].…”
Section: Methodsmentioning
confidence: 99%